Infrastruktur Presiden Jokowi apa gunanya untuk Indonesia? - Amilia, Zakia (Maliki Interdisciplinary Journal, 2024)
This article aims to find out what forms of infrastructure development President Joko Widodo has built in Indonesia. In addition, this article also aims to find out the impact and benefits of the various infrastructures that have been built by President Jokowi during his seven-year reign in Indonesia to date.